2012
DOI: 10.1002/cjoc.201200910
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Michael Addition of Ketone to Alkylidene Malonates Catalyzed by Binaphthyl Sulfonimides in Water

Abstract: Binaphthyl sulfonimides have been developed to catalyze the asymmetric Michael addition of ketone to alkylidene malonates, affording the corresponding Michael products in good to high yields (up to 98%) with good to excellent diastereoselectivity (up to 99:1 dr) and enantioselectivity (up to 92% ee) under mild conditions using environmentally benign water as the solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In 2001, Barbas and coworkers reported the first asymmetric conjugate additions of ketones to alkylidene malonates in moderate to good enantioselectivities using pyrrolidine‐based organocatalyst . Some groups demonstrated the asymmetric Michael addition of ketones to alkylidene malonates using pyrrolidine‐derived urea or thiourea catalyst and sulfonamide organocatalysts . On the contrary, Wang et al reported a thiourea‐sulfonamide organocatalyst that rapidly promoted the conjugate addition of 1,3‐diketones to nitroalkenes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2001, Barbas and coworkers reported the first asymmetric conjugate additions of ketones to alkylidene malonates in moderate to good enantioselectivities using pyrrolidine‐based organocatalyst . Some groups demonstrated the asymmetric Michael addition of ketones to alkylidene malonates using pyrrolidine‐derived urea or thiourea catalyst and sulfonamide organocatalysts . On the contrary, Wang et al reported a thiourea‐sulfonamide organocatalyst that rapidly promoted the conjugate addition of 1,3‐diketones to nitroalkenes.…”
Section: Introductionmentioning
confidence: 94%
“…33,34 Some groups demonstrated the asymmetric Michael addition of ketones to alkylidene malonates using pyrrolidine-derived urea or thiourea catalyst and sulfonamide organocatalysts. [35][36][37][38][39][40] On the contrary, Wang et al 41 reported a thiourea-sulfonamide organocatalyst that rapidly promoted the conjugate addition of 1,3-diketones to nitroalkenes. Thiourea-sulfonamide organocatalysts bearing multiple hydrogen bonding donors were able to efficiently accelerate asymmetric reactions, improving yields and enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC methods for quantitative analysis of S. tridactyla [7] and chemical constituents identified in S. tridactyla [8][9][10], S. medusa [11][12][13][14], S. gossypiphora [15][16][17], and S. laniceps [18,19] are well documented. There is, however, little information about S. aster, S. simpsoniana, S. kingii, and S. quercifolia.…”
Section: Introductionmentioning
confidence: 99%